2009
DOI: 10.1021/ja809947w
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of the Dynamic Process Underlying Allosteric Signal Transmission

Abstract: Allosteric regulation is an effective mechanism of control in biological processes. In allosteric proteins a signal originating at one site in the molecule is communicated through the protein structure to trigger a specific response at a remote site. Using NMR relaxation dispersion techniques we directly observe the dynamic process through which the KIX domain of CREB binding protein communicates allosteric information between binding sites. KIX mediates cooperativity between pairs of transcription factors thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
149
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(161 citation statements)
references
References 49 publications
11
149
0
1
Order By: Relevance
“…4). A similar cooperative mechanism is found in the KIX-MLL-cMyb heterotrimer 45 , in which a two-fold enhancement was linked to an MLL-induced enrichment of the population of the KIX conformer, which has high affinity for cMyb 46 .…”
Section: Discussionsupporting
confidence: 55%
“…4). A similar cooperative mechanism is found in the KIX-MLL-cMyb heterotrimer 45 , in which a two-fold enhancement was linked to an MLL-induced enrichment of the population of the KIX conformer, which has high affinity for cMyb 46 .…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies have observed changes in the KIX structure resulting from transcription factor binding, and both MLL and c-Myb have been shown to allosterically affect the affinity of KIX for the complementary peptide (4,20,(28)(29)(30)(31)(32). However, a connection between the changes in structural dynamics in KIX and how this directly leads to shifts in transcription factor binding affinities remain tenuous.…”
Section: Discussionmentioning
confidence: 99%
“…The binding of either MLL or c-Myb to one of these promiscuous sites can stabilize the C terminus of the α 3 helix of KIX and/or decrease the mobility of the L 12 -G 2 loop (4,20,(28)(29)(30)(31)(32), but the functional role of these changes remains to be delineated. Furthermore, in vitro, KIX alone demonstrates a ∼2-fold lower affinity for c-Myb and ∼1.6-fold lower affinity for MLL compared with KIX bound to MLL or c-Myb, respectively (13).…”
mentioning
confidence: 99%
“…[33][34][35] Numerous examples are currently available highlighting the inextricable link between protein dynamics and allostery 8,36 . Long-range allosteric coupling between sites through changes in internal dynamics were seen between the nucleotide-binding cleft and the preprotein-binding site in SecA ATPase, 37 between the coordination Na þ site and exosite I in thrombin that regulates enzyme's specificity, 38 between the substrate-binding site and distal loop in dihydrofolate reductase, 39 between the mixed lineage leukemia)-and c-Myb binding sites of the KIX domain of CREB-binding protein, 40 in PDZ signaling domains, 41 the serine protease inhibitor eglin c, 42 upon binding of barstar to the RNase barnase, 43 in the interaction between the Rho GTPasebinding domain and Rac1, 44 upon cyclic nucleotide binding to the exchange protein activated by cAMP, 45,46 a in V-type allosteric enzyme, 47 and in protein kinase A, 48,49 only to mention few recent examples from a long list of systems characterized over the years. Dynamic changes in these systems were accompanied by varying extent of structural changes, ranging from minimal to substantial.…”
Section: Dynamics-driven Allosterymentioning
confidence: 99%
“…55 Determining the chemical shifts of the excited state using relaxation dispersion have in several cases provided information that those states structurally resemble related functional states. 40,53,82,83,87 Incorporation of chemical shifts in NMR structure refinement and the development of new NMR experiments that can report on internuclear vector orientations in excited conformational states provide valuable structural constraints that may enable direct structural characterization of higher energy protein conformations. [88][89][90] Kay and coworkers recently reported the structure of an ''invisible'' protein folding intermediate, a remarkable achievement convincingly showing that structure determination of weakly populated conformational states are within reach.…”
Section: Protein Activation Via Energetically Excited Statesmentioning
confidence: 99%